2008
DOI: 10.1111/j.1532-950x.2008.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chondrogenic Potential in Equine Mesenchymal Stromal Cells Derived from Adipose Tissue and Bone Marrow

Abstract: Objective-To compare the chondrogenic potential of adult equine mesenchymal stem cells derived from bone marrow (MSCs) or adipose tissue (ASCs).Study Design-In vitro experimental study. Animals-Adult Thoroughbred horses (n = 11).Methods-BM (5 horses; mean [± SD] age, 4 ± 1.4 years) or adipose tissue (6 horses; mean age, 3.5 ± 1.1 years) samples were obtained. Cryopreserved MSCs and ASCs were used for pellet cultures in stromal medium (C) or induced into chondrogenesis ± transforming growth factor-3 (TGFβ 3 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
5
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 46 publications
8
123
5
4
Order By: Relevance
“…Adipose tissue contains a diversity of cell types, including adipocytes, stromal cells, vascular endothelial cells (ECs), pericytes, and resident blood-derived cells. The higher level of heterogeneity of ASC suggests that those cells do represent MSC that have more lineage capabilities than BM-MSC [16,17]. However, the effects of diabetes on ASC leads to a gradual depletion of the ASC pool, as with BM-MSC [18,19].…”
Section: A B Cmentioning
confidence: 96%
“…Adipose tissue contains a diversity of cell types, including adipocytes, stromal cells, vascular endothelial cells (ECs), pericytes, and resident blood-derived cells. The higher level of heterogeneity of ASC suggests that those cells do represent MSC that have more lineage capabilities than BM-MSC [16,17]. However, the effects of diabetes on ASC leads to a gradual depletion of the ASC pool, as with BM-MSC [18,19].…”
Section: A B Cmentioning
confidence: 96%
“…As in humans, also in veterinary medicine, mesenchymal stem cells (MSCs) have been harvested successfully from a wide range of tissues (Smith et al 2003, Kern et al 2006, Koerner et al 2006, Arnhold et al 2007, Giovannini et al 2008, Vidal et al 2008. The most characterized sources of MSCs are bone marrow (Fortier et al 1998, Ringe et al 2002, Mitchell et al 2003, Smith et al 2003, Kern et al 2006, Vidal et al 2006, Arnhold et al 2007, Vidal et al 2008) and the adipose tissue (Kern et al 2006, Vidal et al 2008; however, the procedures employed to isolate these tissues are still invasive and cells are usually obtained with low efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding aggrecan expression, BMSC respond better to TGFβ, while ASC require BMP-6 (Jakobsen et al, 2009) Human In hyaluronic acid scaffolds chondrogenesis of BMSC was higher compared to ASC (Liu et al, 2007) Human BMSC differentiate better into osteoblasts and chondrocytes, while ASC have higher adipogenic differentiation potential (Afizah et al, 2007) Human BMSC and ASC from the same donor: BMSC are more suitable for cartilage tissue engineering than ASC (Huang et al, 2005) Human A patient-matched study: under the described conditions, BMSC demonstrated a higher chondrogenic potential (Im et al, 2005) Human Results of this study suggest that ASC have inferior capacity for chondrogenic differentiation (Winter et al, 2003) Human There are no differences in the expression of chondrogenic marker genes in 2D cultures between ASC and BMSC. In 3D cultures BMSC expressed a gene profile similar to that of osteoarthritic cartilage (Koga et al, 2008) Rabbit BMSC have higher chondrogenic potential compared to ASC in vitro and in vivo Rat There are no major differences between ASC and BMSC regarding the chondrogenic differentiation potential (Kisiday et al, 2008) Equine Superior chondrogenesis of BMSC was demonstrated in comparison to ASC (Vidal et al, 2008) Equine Superior chondrogenesis of BMSC was demonstrated in comparison to ASC Table 2. Differences in surface marker expression of HLA-ABC in BMSC, making ASC more suitable for allogenic transplantations.…”
Section: Referencementioning
confidence: 98%
“…A considerable number of papers have been published since 2003, addressing the question of which cell type, ASC or BMSC, possesses a higher chondrogenic potential (Table 1). A variety of authors concluded that BMSC can be more easily differentiated towards the chondrogenic lineage than ASC (Afizah et al, 2007;Danisovic et al, 2009;Huang et al, 2005;Im et al, 2005;Jakobsen et al, 2009;Kisiday et al, 2008;Koga et al, 2008;Liu et al, 2007;Vidal et al, 2008). However, Diekman et al (2010) pointed out that ASC and BMSC require unequal growth factor treatment for chondrogenic induction.…”
Section: The Potential Of Msc To Improve the State Of The Artmentioning
confidence: 99%